2022
DOI: 10.1016/j.crmicr.2021.100101
|View full text |Cite
|
Sign up to set email alerts
|

A potent cadmium bioaccumulating Enterobacter cloacae strain displays phytobeneficial property in Cd-exposed rice seedlings

Abstract: Highlights Cd-resistant and halotolerant PGPR enterobacter cloacae AS10 was isolated. AS10 showed IAA, HCN production, P-solubilization, N 2 fixation, ACCD activity. AAS-TEM-EDAX-XRD-XRF-FTIR studies confirmed Cd bioaccumulation by AS10. AS10 reduced oxidative stress, Cd uptake and improved rice seedling growth in vitro .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Moreover, Abdollahi et al ( 2020 ) have reported that E. cloacae had MIC 3000 ug/ml and 50 ug/ml against Pb +2 and Cd +2 with accumulation capacity 45ug Pb +2 /ml and 30ug Cd +2 /ml. Also, Ghosh et al ( 2022 ) have reported that E. cloacae expressed a high potency of tolerance towards high concentrations of Cd +2 (4000 μg/ml), Pb +2 (3312 μg/ml), and As +3 (1500 μg/ml), where the removal efficiency of Cd +2 was recorded 72.11% (Abdollahi et al, 2020 ; Ghosh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Abdollahi et al ( 2020 ) have reported that E. cloacae had MIC 3000 ug/ml and 50 ug/ml against Pb +2 and Cd +2 with accumulation capacity 45ug Pb +2 /ml and 30ug Cd +2 /ml. Also, Ghosh et al ( 2022 ) have reported that E. cloacae expressed a high potency of tolerance towards high concentrations of Cd +2 (4000 μg/ml), Pb +2 (3312 μg/ml), and As +3 (1500 μg/ml), where the removal efficiency of Cd +2 was recorded 72.11% (Abdollahi et al, 2020 ; Ghosh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress disturbs physiological and metabolic processes of the plants leading to a limitation in plant growth, crop production and yield, and consequently causes massive agricultural loss (Tran and Popova 2013 ). Recently, plant root-associated bacteria are globally used for the amelioration of crop performance to encounter heavy metal contamination in agricultural soils (Mitra et al 2018 ; He et al 2020 ; Ghosh et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This crucial aspect considered as an interest gateway for scientists to search novel cost effective and eco-friendly methods to alleviate the abiotic stresses in field grown plants. The application of bacteria to mitigate stress-induced negative impact in plants and their role to make plants tougher toward abiotic stresses have been documented (Panlada et al 2013 ; Nadeem et al 2014 ; Kaushal and Wani 2016 ; Rizvi and Khan 2018 ; Ghosh et al 2022 ). In this study, the efect of S. maltophilia EPS inoculation on the antioxidant defense of safflower plants ( Carthamus tinctorius L.) exposed to different levels of Cd was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Associated with HM, these intracellular proteins can also lower the concentration of free ions in the cytoplasm where metal detoxification has occurred ( Etesami, 2018 ). A study by Ghosh et al (2022) reported that Enterobacter cloacae can remove HMs through a bioaccumulation process. The efficiency of HMs accumulation depends not only on the internal structure of the cell and space, genetic characteristics, and cellular processes for enzymatic catalysis, but also on the location from which the bacterial strain is isolated, in natural areas with extreme conditions or grows with adaptation in a contaminated place ( Pham et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%